2019
DOI: 10.33365/ts.v15i2.102
|View full text |Cite
|
Sign up to set email alerts
|

Predicates of Indonesian and English Simple Sentences

Abstract: This paper was developed from a research report presented in The Third Southern Region of Sumatera TEFLIN held by Sriwijaya University in 2014. Comments recieved by the participants of the seminar and following studies done on the topic made it possible for this article to find its way to be published in a journal. As Indonesian and English sentences realize their predicates by using different kinds of syntactic categories, most learners of English having Indonesian as their linguistic background face difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Therefore, a non-verbal predicate can be noun, adjective, preposition, adverbial, and number. The result of this study is supported by the previous study conducted by Gulö (2019) and Kartika et al (2019), who found that the predicates in the Indonesian language can be in the form of verbs, adjectives, and nouns. Specifically, Moeljadi et al (2016) found that there are three types of the basic copula in Indonesian, they are Noun Phrase (NP), Adjective Phrase (AP), and Prepositional Phrase (PP) that may occur without a copula verb.…”
Section: Finding and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, a non-verbal predicate can be noun, adjective, preposition, adverbial, and number. The result of this study is supported by the previous study conducted by Gulö (2019) and Kartika et al (2019), who found that the predicates in the Indonesian language can be in the form of verbs, adjectives, and nouns. Specifically, Moeljadi et al (2016) found that there are three types of the basic copula in Indonesian, they are Noun Phrase (NP), Adjective Phrase (AP), and Prepositional Phrase (PP) that may occur without a copula verb.…”
Section: Finding and Discussionsupporting
confidence: 86%
“…Table 3 shows that the predicate is filled by adjective phrase sangat lesu 'very weak' in (12), masih buka 'still open' in (13), benar-benar steril 'completely sterile' at (15), harus jelas 'must be clear' in (16), and adjective sakit 'sick' in (14), takut 'scare' in (17). All the adjective predicates require one argument that functions as the subject of the sentence.…”
Section: Adjective As Predicatementioning
confidence: 99%
See 1 more Smart Citation
“…It is part of a bilingual edition of short stories (Indonesian and English). Accordingly, (Gulö, 2019) argues that an alternative method to collect data from the existing document is the content-analysis method. Moreover, (Kothari, 2004) posits that the content-analysis method is an appropriate way to study the message in an existing document or verbal material.…”
Section: Methods Of Researchmentioning
confidence: 99%
“…Furthermore, to find data in the passages, this research applied documentary search (Atkinson and Coffey, 2004). Furthermore, this research used content analysis to collect data from the existing document (Gulo, 2017).…”
Section: Methodsmentioning
confidence: 99%